Comparison of surgical outcomes between patients undergoing trans-oral endoscopic thyroid surgery combined with trans-thoracoareolar approach and conventional open surgery - Shi, Youyuan; Zhang, Lu; Liu, Chang; Wang, Yong; Zhang, Hailin; Lin, Xiuan (Frontiers in Surgery, 2022)
Over the past decades, remote-access thyroid surgery has been widely developed in the treatment for thyroid carcinoma, which can help patients to avoid cosmetically displeasing scarring. In this research, we collected and review our experience with endoscopic TND via trans-thoracoareolar approach combined with trans-oral approach over a 3-year period. They were all diagnosed with thyroid carcinoma, two of them had a complication of Hashimoto's thyroiditis. No patients was dissatisfied with the postoperative cosmetic results. One patient had numbness in lower lip, but the symptom disappeared one month later. No infection, hemorrhage or air embolism occurred. Pain and numbness in endoscopic thyroid surgery group were slighter than those who had open surgery. The aim of present study was to compare the feasibility and safety of Trans-thoracoareolar approach combined with trans-oral approach to conventional open surgery.